1992
DOI: 10.1021/bi00135a008
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and modeling studies of S3-S3' subsites of HIV proteinases

Abstract: Kinetic analysis and modeling studies of HIV-1 and HIV-2 proteinases were carried out using the oligopeptide substrate [formula: see text] and its analogs containing single amino acid substitutions in P3-P3' positions. The two proteinases acted similarly on the substrates except those having certain hydrophobic amino acids at P2, P1, P2', and P3' positions (Ala, Leu, Met, Phe). Various amino acids seemed to be acceptable at P3 and P3' positions, while the P2 and P2' positions seemed to be more restrictive. Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 47 publications
4
38
0
Order By: Relevance
“…3), and Partin et al (34) observed that Phe readily substituted for Tyr at this site. Both increased and decreased rates of cleavage for a P1 Phe have been reported for equivalent peptide substrates of the MA/CA site (3,54).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…3), and Partin et al (34) observed that Phe readily substituted for Tyr at this site. Both increased and decreased rates of cleavage for a P1 Phe have been reported for equivalent peptide substrates of the MA/CA site (3,54).…”
Section: Discussionmentioning
confidence: 78%
“…The amino acids flanking the target scissile bond are generally hydrophobic (16,33,37). A number of studies have used peptide or Gag substrates in an attempt to define the role of specific amino acids at different positions flanking the scissile bond as they impact the rate of cleavage by the viral protease (3,5,13,14,19,30,34,36,38,44,45,51,(53)(54)(55); recently reviewed in reference 27). In the present study we have examined the ability of approximately 15 different amino acids in the P1 position of the five different Gag cleavage sites to support cleavage by the HIV-1 protease (the P1 position is the amino acid immediately upstream of the scissile bond, and the P1Ј position is the amino acid immediately downstream of the scissile bond).…”
mentioning
confidence: 99%
“…The prediction error for the cleavage rates was less than one log(k cat /K m ) unit for 68% of the protease-substrate pairs; the correlation for the a priori predicted rates versus the experimentally determined rates yielding a correlation coefficient r ¼ 0. 47 (Table S1), but excluded all data for the proteases of one retroviral strain, one at a time, and uses the model to predict the excluded data. Blue bullets correspond to prediction of cleavage activity for new proteases and new substrates (i.e., the cases in which neither the protease nor the peptide was represented in the dataset used in creation of the model).…”
Section: Author Summarymentioning
confidence: 99%
“…The dissolved proteins were fractionated by reverse-phase high-pressure liquid chromatography (RP-HPLC) on a 19x 150mm g-Bondapack C18 column (Waters Associates) with a linear gradient of 0.60% acetonitrile in the presence of 0.05 % TFA in water as previously described (Copeland & Oroszlan, 1988). Fractions from the RP-HPLC column were lyophilized, dissolved in 2 M-guanidine hydrochloride and 100 mM-Tris-HC1 pH 8.0 at a concentration of 200-300 gg/ml, and refolded as previously described (Tozser et al, 1992). Briefly, one volume of protein solution was diluted with two volumes of refolding buffer (20 mM-PIPES pH 7.0, 100 mM-NaC1, 10% glycerol, 1 mM-EDTA).…”
Section: Purification Of Prmentioning
confidence: 99%